Cutaneous Manifestations of Thyroid Hormone Disorder - Sijapati, Karuna Singh; Rijal, Arpana; Agrawal, Sudha; Khadka, Dhan Keshar; Maskey, Robin (Nepal Journal of Dermatology, Venereology & Leprology, 2019)
Introduction: Thyroid hormone disorder (THD), a major health problem, is associated with a wide range of diseases. One of the organs, which shows this wide range of clinical signs is the skin. Some dermatological findings may be the first symptoms of THD. Therefore, this study was planned to determine various cutaneous manifestations of THD that can be used as a diagnostic marker for THD. In Nepal due to lack of awareness, thyroid diseases may go unnoticed .So, cutaneous manifestations help in early diagnosis and treatment of THD. Objectives: To identify cutaneous manifestations of THD and to evaluate dermatological manifestations specific for THD. Materials and methods: Seventy six patients with diagnosis of THD attending endocrine clinic of Internal Medicine Department in BPKIHS, Dharan were consecutively assessed for cutaneous changes by detailed history and clinical examination. As a control group, 26 age and sex matched individuals without THD were included to assess frequency of cutaneous manifestation in normal individuals. Results: Fifty five (72.3%) cases and 4(15.4%) control had skin changes. This observation was statistically significant with OR-14.4(95% CI4.43 – 46.78) and p<0.001.Hair changes (OR-2.100, 95% CI 0.647-6.821 and p=0.210) and nail changes (OR-1.818, 95% CI 0.371-8.902 and p=0.726) had no statistically significant association with THD. Conclusion: THD may present as or be associated with many changes in skin, hair and nails.